2021
DOI: 10.1021/acs.energyfuels.1c01035
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Review on the Application of Nanomaterials in Improving Anti-Aging Properties of Asphalt

Abstract: Exposed to detrimental environmental factors, such as heat, oxygen, and ultraviolet (UV) radiation, asphalt materials are prone to hardness and brittleness, namely, asphalt aging, which leads to deteriorating asphalt pavement properties and inducing a series of road distress. Theoretical and experimental studies have demonstrated that nanomaterial modifiers are a promising solution. This review discusses the application of single, compounded, and composited nanomaterial modifiers in improving the aging resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(21 citation statements)
references
References 126 publications
(317 reference statements)
0
21
0
Order By: Relevance
“…erefore, taking measures to actively inhibit the aging of asphalt is a better choice for building tough and durable road facilities. Current asphalt antiaging technologies, such as the incorporation of layered silicates and layered double hydroxides (LDHs) compounds, face the challenges of high cost and poor compatibility with asphalt, making them difficult to apply in engineering practice on a large scale [15,16]. In contrast, phenolic antioxidants from natural sources such as catechin, gallic acid, and lignin are widely available and have a similar molecular structure to asphalt, thus avoiding these disadvantages and becoming a promising raw material for the development of efficient asphalt antiaging technology [17].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, taking measures to actively inhibit the aging of asphalt is a better choice for building tough and durable road facilities. Current asphalt antiaging technologies, such as the incorporation of layered silicates and layered double hydroxides (LDHs) compounds, face the challenges of high cost and poor compatibility with asphalt, making them difficult to apply in engineering practice on a large scale [15,16]. In contrast, phenolic antioxidants from natural sources such as catechin, gallic acid, and lignin are widely available and have a similar molecular structure to asphalt, thus avoiding these disadvantages and becoming a promising raw material for the development of efficient asphalt antiaging technology [17].…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional network structure formed by a styrene-butadiene-styrene triblock copolymer (SBS) in bitumen can render SBS-modified bitumen (SBSMB) extraordinary high- and low-temperature performance. , Nevertheless, when affected by aging factors like heat, oxygen, and ultraviolet radiation during the preparation and service period of bitumen materials, the butadiene block, an essential part of triblock structure of SBS, tends to be destroyed and oxidized, resulting in the fracture of copolymer chains. In addition, the bitumen matrix also suffers irreversible constituent transformation from maltenes to asphaltene due to a series of reactions (volatilization, oxidation, condensation, polymerization, etc.) caused by thermal or photo-oxidation aging. Both of the changes in polymer modifier and bitumen matrix can give rise to serious performance deterioration and service time decline of SBSMB pavement. , The renovation and reconstruction of the old or out-of-service pavement need to deplete unrenewable mineral and petroleum resources while creating a large amount of road waste materials.…”
Section: Introductionmentioning
confidence: 99%
“…With the volatilization of lightweight components during the aging process, the asphalt binder becomes harder and brittle rapidly [ 8 ]. The increasing brittleness of an asphalt binder can reduce its tensile strength and fatigue resistance, becoming prone to cracks under low-temperature or repeated loading conditions [ 9 , 10 , 11 ]. The aging process also reduces the adhesion performance of the asphalt mixtures [ 12 ].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Other studies also indicated that, when nano-ZnO particles are incorporated into asphalt binder, the viscosity aging index and the mass loss of the modified asphalt binder were inferior to those of the unmodified one after UV aging conditions [ 33 , 34 , 35 ]. Moreover, the introduction of nano-ZnO particles and expanded vermiculite in the asphalt binder improved its resistance to thermo-oxidative and UV aging at the same time, reducing the deterioration rates of the modified asphalt binder [ 11 , 26 , 32 , 36 ].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation